Outcome of the Compensation Process Initiated by an Occupational and Environmental Diseases Center - Scherer, Mathilde; Lamouroux, Celine; Fiquemont, Alizée; Fassier, Jean-Baptiste; Gautheron, Laure; Massardier-Pilonchéry, Amélie; Charbotel, Barbara (La Medicina del Lavoro, 2024)
Background: Regional Centers for Occupational and Environmental Pathologies (CRPPE) are responsible for identifying possible occupational etiologies of pathologies. When an occupational origin is determined, an Initial Medical Certificate (IMC) is given to the patient to allow him to initiate a procedure for recognition as an occupational disease (OD) by his health insurance organization. Objectives: The main aim of this study was to investigate the outcome of occupational disease claims in patients who received an IMC delivered by the CRPPE of Lyon. Methods: A telephone interview was systematically conducted with patients who consulted the CRPPE for a claim for occupational disease recognition between 07/2020 and 06/2021, about six months after the consultation. It was conducted by a physician using a standardized questionnaire. Results: Out of 128 patients eligible for this study, 98 were included. Diseases of the respiratory system (34.7%) and cancers (28.6%) were the most common pathologies in our population. A process of OD compensation was initiated by 86 patients (87.8%). At the time of the study, the outcome was favorable for 63 patients (73.3%). Moreover, 18 patients (18.4%) wished for additional help from the CRPPE to carry out the procedures. Nine patients requested a new consultation, including five who still needed to complete the process. Conclusion: This study shows the benefit of a consultation by occupational disease consultants. However, difficulties still need to be solved in these procedures. Thus, the systematic follow-up of patients shows its advantages. The provision of support to carry out the process seems necessary.